2000
DOI: 10.1093/jn/130.2.443s
|View full text |Cite
|
Sign up to set email alerts
|

Anemia, Iron and Pregnancy Outcome

Abstract: When maternal anemia is diagnosed before midpregnancy, it has been associated with an increased risk of preterm delivery. Maternal anemia detected during the later stages of pregnancy, especially the third trimester, often reflects the expected (and necessary) expansion of maternal plasma volume. Third-trimester anemia usually is not associated with increased risk of preterm delivery. High hemoglobin concentration, elevated hematocrit and increased levels of serum ferritin late in pregnancy, however, all have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
139
0
13

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(159 citation statements)
references
References 23 publications
7
139
0
13
Order By: Relevance
“…However, the difference of 0.6 weeks might not be biologically significant. In contrast to findings from observational studies (Allen, 2000;Scholl & Reilly, 2000), controlled trials on iron supplementation do not provide evidence for benefits on preventing intrauterine growth retardation (de Onis et al, 1998a,b). Preziosi et al (1997) showed that infants of iron supplemented mothers were longer, but not heavier, at birth than those of nonsupplemented mothers.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, the difference of 0.6 weeks might not be biologically significant. In contrast to findings from observational studies (Allen, 2000;Scholl & Reilly, 2000), controlled trials on iron supplementation do not provide evidence for benefits on preventing intrauterine growth retardation (de Onis et al, 1998a,b). Preziosi et al (1997) showed that infants of iron supplemented mothers were longer, but not heavier, at birth than those of nonsupplemented mothers.…”
Section: Discussionmentioning
confidence: 86%
“…Risk of preterm delivery and low birth weight are associated with iron deficiency anaemia during pregnancy (Scholl & Reilly, 2000). The addition of vitamin A to routine iron supplementation has been shown to increase haemoglobin concentrations during pregnancy (Suharno et al, 1993, Muslimatun et al, 2001.…”
mentioning
confidence: 99%
“…At least 50% of the anemia has been attributed to iron deficiency (DeMaeyer and Adiels-Tegman, 1985;Singh et al, 1998). Maternal iron deficiency anemia increases the risk of premature delivery and subsequent low birth weight, and may contribute to low iron status and poor health of infants (Allen, 2000;Scholl and Reilly, 2000;Kaiser and Allen, 2002). Also, pregnant women with anemia are at a greater risk of perinatal mortality and morbidity (Haas and Brownlie, 2001;Rasmussen, 2001;Ramakrishnan and Yip, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Yapılan bazı çalışmalarda, gebelerdeki demir eksikliğinin, fetus ve infarıtın demir durumunu etkilediği, prematür doğum prevalansını artırdığı, uzun dönemde büyüme ve gelişme geriliğine neden olabileceği gösteril-miştir (5)(6)(7)(8). Bazı çalışmalarda da annenin demir durumunun bebeğin demir durumuna etkisi olmadığı, bebeklerin demir depolannın ilk dört ay için yeterli olduğu bildirilmiştir (9-1 1).…”
Section: Ssk Tepecik Hast Derg 2004;14(3)g153-162unclassified